2019
DOI: 10.1002/mc.23025
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA promotes the malignant transformation of gastric mucosal epithelial cells through the dysregulation of the miR‐155/KLF4 signaling pathway

Abstract: The Helicobacter pylori (H. pylori) cytotoxin-associated gene A (CagA) and Krüppel-like transcription factor (KLF4) were both closely associated with the development and progression of gastric cancer (GC). However, the nature of the interactions between CagA and KLF4 in GC development has not been elucidated. Therefore, we focused on the CagA-mediated promotion of the malignant transformation of gastric epithelial cells. Herein, we first examined the expression of KLF4 in both human cancer and paracarcinoma ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 46 publications
(49 reference statements)
1
36
0
Order By: Relevance
“…Qu Y et al showed that miR-155 downregulated the expression of TGFβR2 to promote the proliferation and migration of GC cells, which is consistent with our study [40]. Moreover, it was reported that Helicobacter pylori infection was closely linked to miR-155, possibly upregulating miR-155 expression to inhibit the DNA mismatch repair (MMR) gene and induce a mutant phenotype that is conducive to error-prone translation synthesis and thus promotes GC progression [41][42][43]. However, some studies have reported that miR-155 is expressed at low levels in GC tissue and acts as a tumor suppressor gene [44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…Qu Y et al showed that miR-155 downregulated the expression of TGFβR2 to promote the proliferation and migration of GC cells, which is consistent with our study [40]. Moreover, it was reported that Helicobacter pylori infection was closely linked to miR-155, possibly upregulating miR-155 expression to inhibit the DNA mismatch repair (MMR) gene and induce a mutant phenotype that is conducive to error-prone translation synthesis and thus promotes GC progression [41][42][43]. However, some studies have reported that miR-155 is expressed at low levels in GC tissue and acts as a tumor suppressor gene [44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study has demonstrated an increased migration and proliferation rate of cells transfected with CagA, suggesting its role in promoting the malignant transfection of gastric epithelial cells [ 85 ]. Several studies have found an enhanced probability of gastric carcinogenicity and an induction of the epithelial mesenchymal transition (EMT) process caused by CagA-positive H. pylori [ 86 , 87 , 88 ].…”
Section: Caga-dependent Mechanisms Of Pathogenicitymentioning
confidence: 99%
“…Interestingly, Helicobacter pylori (H. pylori) and its cytotoxin-associated gene A (CagA) were shown to promote malignant transformation of gastic mucosal epithelial cells. H. pylori impairs DNA mismatch repair and facilitates tumor growth through the induction of miR-155, suggesting that H. pylori, at least partly, mediates carcinogenesis through miR-155 expression in gastric cancer [51,52]. Additionally, H. pylori has been reported to promote carcinogenesis via miR-155 upregulation in a model of gastric mucosa-associated lymphoid tissue (MALT) lymphoma [53].…”
Section: Dysregulation Of Mirs In Ctclmentioning
confidence: 99%